2022
DOI: 10.4149/bll_2022_019
|View full text |Cite
|
Sign up to set email alerts
|

Critical care for lung cancer patients: surgical treatment during COVID-19 pandemic

Abstract: BACKGROUND: During the COVID-19 pandemic, some factors have led to changes in the management of patients with lung cancer. In our study, we aimed to present our surgical treatment approach to patients with NSCLC during the COVID-19 pandemic. METHODS: Patients who underwent surgery for NSCLC in our thoracic surgery clinic between March 2020 and March 2021 were evaluated retrospectively. The patients operated on were retrospectively evaluated in terms of sex, age, tumor staging, lung resection type, histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Using these three substages, doctors assign the stage of a patient's cancer by combining the T, N, and M classifications in overall stages [ 22 24 ]. The combinations for cancer specifically are outlined here.…”
Section: Background Studymentioning
confidence: 99%
“…Using these three substages, doctors assign the stage of a patient's cancer by combining the T, N, and M classifications in overall stages [ 22 24 ]. The combinations for cancer specifically are outlined here.…”
Section: Background Studymentioning
confidence: 99%
“…An analogous study consisting of 35 NSCLC patients undergoing surgical resection at a single centre in Turkey from 2020 to 2021 reported 0% and 14% rates of postoperative mortality and morbidity, respectively. There was no significant difference in complications in patients with a preoperative history of COVID-19 [ 41 ]. Finally, utilizing the Polish National Lung Cancer Registry, Piwkowski et al [ 25 ] reported a 20.5% overall reduction in the number of lung cancer procedures, with no difference in rates of in-hospital mortality and decreased hospital length of stay during the pandemic.…”
Section: Resultsmentioning
confidence: 99%